Determination of Folic Acid by Solid-Phase Extraction and Flow Injection Chemiluminescence - Zhao, Shi-Hao; Zhang, Ping-Ping; Zhao, Shi-Bin (Asian Journal of Chemistry, 2010)
Based on the chemiluminescence emitting reaction between cerium(IV) sulfate and sodium sulfite in acid medium, enhanced with folic acid. A simple, rapid, accurate and sensitive method of solid-phase extraction and flow injection chemiluminescence was developed for the determination of folic acid. The optimized experimental conditions were evaluated. Under optimum conditions, calibration curve over the range of 0.1-7.0 μg L-1 was obtained. The detection limit of this method was 0.02 μg L-1. The relative standard deviation was 3.9 % for 1.0 μg L-1 folic acid. The method has been applied to the determination of studied folic acid in infant formula milk powder with satisfied result.